Rhythms of intuition. Methodological reflections in phenomenological psychology - Kudahl, Benedikte; Roald, Tone (Qualitative Studies, 2021)
This paper discusses how different concepts of rhythm apply to phenomenological psychological research. We suggest that viewing phenomenological research in psychology as rhythmic not just enables us to notice how the research procedure implies certain shifts within in a series of temporally structured movements of repetition and change; it also enables us to deepen our understanding of the manner in which the researcher engages with the studied phenomenon through intuition. In other words, we argue that rhythm is fundamental to the method of how we understand “the things themselves.”